New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda) - Mikhaljova, Elena V. (Zootaxa, 2020)
Seven new species of the millipede genus Nepalmatoiulus Mauriès, 1983 (Julidae) are described from China: N. sichuanensis sp. nov., N. chinensis sp. nov., N. muli sp. nov., N. tianbaoshanensis sp. nov., N. pallidus sp. nov., N. weixi sp. nov., N. immaturus sp. nov. One species of the genus Anaulaciulus Pocock, 1895 is new for the Chinese fauna: A. inaequipes Enghoff, 1986.